Advantages of Using Blend Cultures of Native L. plantarum and O. oeni Strains to Induce Malolactic Fermentation of Patagonian Malbec Wine - Brizuela, Natalia S.; Bravo-Ferrada, Bárbara M.; Curilén, Yolanda; Delfederico, Lucrecia; Caballero, Adriana; Semorile, Liliana; Pozo-Bayón, M. Ángeles; Tymczyszyn, E. Elizabeth (Frontiers in Microbiology, 2018)
The malolactic fermentation (MLF) of Patagonian Malbec wine inoculated with blend cultures of selected native strains of Lactobacillus plantarum and Oenococcus oeni was monitored during 14 days, analyzing the strains ability to modify the organic acids content and to change the volatile compounds profile. The performance of the LAB strains was tested as individual and blend cultures of both species. An implantation control by RAPD PCR was also carried out to differentiate among indigenous and inoculated strains. The L. plantarum strains UNQLp11 and UNQLp155 and the O. oeni strain UNQOe73.2 were able to remain viable during the monitoring time of MLF, whereas the O. oeni strain UNQOe31b showed a decrease of 5 log CFU at day 14. The four strains assayed showed a similar behavior in wine whether they were inoculated individually or as blend cultures. All strains were able to consume the L-malic acid, particularly the L. plantarum strains, which showed the highest consumption values at day 14, both as individual or blend cultures. The changes in the volatile compounds profile of Malbec wine samples, before and after MLF, were determined by HS-SPME and GC-MS technique. Wines inoculated with blend cultures containing the strain UNQLp155 showed a decrease in the total alcohols concentration and an increase in the total esters concentration. On the other hand, wines inoculated with single cultures of strains UNQLp155, UNQOe31b or UNQOe73.2 showed no significant decrease in the total alcohols concentration but a significant increase in the total esters concentration. When the strain UNQLp11 was inoculated as simple culture or as blend culture with the strain UNQOe31b, wines exhibited an increase in the total alcohols concentration, and a decrease in the total esters concentration. The diethyl succinate content exhibited the most notable increase at final of MLF, and a particular synergistic effect in its synthesis was observed with a blend culture of strains UNQLp155 and UNQOe73.2. These results suggest that the use of blend cultures formulated with strains belonging to L. plantarum and O. oeni species could offer an interesting advantage to induce MLF in Malbec wines, contributing to diversify their aromatic profiles.